Production gradients in smallholder banana (cv. Giant Cavendish) farms in Central Kenya - Okumu, MO; Asten, Piet J.A. van; Kahangi, EM; Okech, SH; Jefwa, J.M.; Vanlauwe, Bernard (Elsevier, 2011)
Banana is an increasingly demanded food and cash crop in sub-Saharan Africa. Reported yields in smallholder farms vary substantially. The importance and spread of yield constraints have not been properly quantified. A study was carried out in Central Kenya to (i) quantify the yield levels, the primary yield constraints, and the spatial production gradients in such systems (ii) explore how soil fertility gradients relate to gradients in soil fertility management, and whether this is a function of farmer resource availability. Data was collected on crop management aspects, pests and diseases, and soil and plant tissue samples analyzed for nutrient contents. Bunch yields were higher near homesteads (29.8 t ha?1 yr?1) than at mid-distance (26.8 t ha?1 yr?1), or far away 20.2 t ha?1 yr?1. Yields were much higher than previously reported (11 14 t ha?1 yr?1) in Kenya. Both soil and tissue K levels were higher near and mid-distance, than far from the homestead. Gradients of soil pH, total N, available P and Organic carbon were found, being higher near the homestead, while Mg and Ca were lowest near the homesteads. K was the most deficient nutrient, with tissue K index (IK) decreasing when moving away from the homesteads. P and Ca deficiencies were also observed. Resource-poor farmers soils were higher in exchangeable K and Mg, pH, and total N, and supported higher mat densities compared to resource-endowed farmers farms. Soil quality problems were the biggest yield loss factors and not pests and diseases.